Epidemiology and Screening of Developmental Dysplasia of the Hip in Europe: A Scoping Review - Emmanuela Dionysia Laskaratou; Anna Eleftheriades; Ioannis Sperelakis; Nikolaos Trygonis; Periklis Panagopoulos; Theodoros H. Tosounidis; Rozalia Dimitriou (Reports, 2024)
Developmental hip dysplasia or developmental dysplasia of the hip (DDH) includes a wide range of deformities of the hip, such as congenital dysplasia, subluxation, and dislocation. It is usually identified through neonatal screening during the first 6–8 weeks of life. The incidence of DDH ranges from 1–7% in neonates among some populations, but this may vary among different ethnicities and countries. A consensus about the ideal age for screening has not been reached to date. The aim of this study is to summarize the existing data regarding the incidence of congenital hip dysplasia and screening tests among European countries. The authors conducted a systematic search in PubMed/Medline and Scopus and collected original studies published in English, French or German. The incidence of DDH presents fluctuations, not only among European countries, but also within the same country. There is no unanimity regarding the screening methods of DDH; in some countries, universal ultrasound is proposed as the basic screening method for neonates for DDH; in other countries screening is performed only in high-risk cases. More robust data are needed to conclude which screening approach is associated with improved long-term outcomes.